Acute physiological responses and performance determinants in Hyrox© – a new running-focused high intensity functional fitness trend - Brandt, Tom; Ebel, Cindy; Lebahn, Christopher; Schmidt, Annette (Frontiers in Physiology, 2025)
AimsHyrox© is a fitness modality combining 8 functional exercises with running in a comprehensive competition format. Within this first scientific study on Hyrox©, acute physiological responses, relative perceived exertion (RPE), and possible performance determinants were assessed during a simulated Hyrox© competition to derive training recommendations and potential practical applications.MethodsEleven recreational Hyrox© athletes [27% women, Hyrox© experience median (interquartile range): 18 (19) months] participated. In a pre-test, height, body composition, hand grip strength (HGS), maximum oxygen consumption (VO2max), and volume of resistance and endurance training were assessed. After 48 h rest, a simulated Hyrox© was conducted according to the competition-standards of the “Individual Open Division”. Heart rate (HR) was tracked throughout the Hyrox©. Blood lactate (BL) and RPE were recorded at the beginning and after each run and exercise station. Differences between runs and exercise stations for HR, BL, and RPE were analyzed via Wilcoxon signed rank test. Spearman’s rank correlation test was conducted to identify associations between completion times (Hyrox©, runs, exercise stations) and participant characteristics. Values are given as median (interquartile range).ResultsCompletion time of the Hyrox© was 86.5 (14.5) minutes, whereby runs (51.2 (14.1) minutes) were significantly longer than the exercise stations [32.8 (6.1) minutes] (p = 0.003). Most of the Hyrox© was performed at very hard and hard intensities [79.5 (21)% and 19.6 (20.7)% of maximum HR]. Maximum BL was higher during the exercise stations [8.5 (5.4) mmol/L] compared to the runs (7.7 (4.6) mmol/L) (p = 0.006). Similar results were found for maximum RPE [exercise stations: 18 (2), runs: 16 (2), p = 0.003]. The highest values for HR, BL, and RPE occurred during the last exercise (wall balls). The exercise stations with the heaviest loads were completed the fastest [sled push: 128 (34) seconds, sled pull: 155 (38) seconds]. Faster Hyrox© completion correlated significantly with higher VO2max (p = 0.01), greater endurance training volume (p = 0.04), and lower body fat percentage (p = 0.03).ConclusionHyrox© is a HIFT modality with an emphasis on endurance capacity and moderate to low requirements in terms of maximum strength, coordination, and mobility when compared to other forms HIFT. Hyrox© may be suitable for health promotion and tactical population training.